AGT M235T variant is not associated with risk of cancer. (June 2015) - Lin, Jianjun; Chen, Jiayu; Liu, Chibo
Objective: The angiotensinogen ( AGT ) gene has been considered to be implicated in the development of cancer. However, the results have been inconsistent. In this study, we performed a meta-analysis to clarify the association of AGT M235T variant with cancer risk. Methods: Published literature from PubMed and Embase were retrieved. Pooled odds ratio (OR) with 95% confidence interval (CI) was calculated using a fixed- or random-effects model. Results: A total of seven articles including eight studies (3639 cancer cases and 6684 controls) for AGT M235T variant were included. The present meta-analysis showed that AGT M235T variant was marginally associated with cancer risk under dominant model (OR=1.12, 95% CI=1.02–1.24). However, the positive association was not stable after sensitivity analysis. Further subgroup analysis by cancer type did not suggest any association of AGT M235T variant with various cancers (all p >0.05). Conclusion: The present meta-analysis demonstrated that AGT M235T variant was not associated with risk of all cancer or various cancers. Further well-designed studies with large sample size should be conducted to confirm or refute the non-significant association.